2018
DOI: 10.15296/ijwhr.2019.61
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sexual Counseling Based on PLISSIT Model on Sexual Function of Pregnant Women: A Randomized Controlled Clinical Trial

Abstract: Objectives: Several factors, including pregnancy which is associated with physical, psychological, and hormonal changes, affect females and their sexual partners’ relation and function. This study aimed to investigate the effect of "permission, limited information, specific suggestions, intensive therapy" (PLISSIT)-based sexual counseling on the sexual function of pregnant women. Materials and Methods: The present randomized controlled trial was performed on 70 pregnant women who had a sexual function score of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…This interesting finding is inconsistent with previous studies, which reported the permission level was the first or core level of the PLISSIT model among Iranian women who became pregnant naturally and in an assessment of the perspectives of nurses in Taiwan. 23 , 37 Patients in eastern medical services may possibly have less authority at the permission level owing to the medical professional–centered paradigm of health care. 38 This finding provides a reminder of how nurses could actively provide SHC education in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This interesting finding is inconsistent with previous studies, which reported the permission level was the first or core level of the PLISSIT model among Iranian women who became pregnant naturally and in an assessment of the perspectives of nurses in Taiwan. 23 , 37 Patients in eastern medical services may possibly have less authority at the permission level owing to the medical professional–centered paradigm of health care. 38 This finding provides a reminder of how nurses could actively provide SHC education in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…PLISSIT-based counseling can reduce sexual problems and increase the sexual function of pregnant women. 23 Nurses must pay more attention to the negative impact of reduced sexual function among pregnant women and actively provide appropriate, comprehensive SHC suggestions in the clinic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The permission, limited information, specific suggestions, and intensive therapy (PLISSIT) model created by Jack S. Annon, in 1976, is also known as the PLISSIT model of sex therapy. This model is one of the most frequently used designs by health professionals for sexual assessment and counseling to determine the different levels of intervention for individual clients (Shahbazi, et al, 2018;Annon, 1976).…”
Section: Introductionmentioning
confidence: 99%